2010
DOI: 10.4049/jimmunol.0902778
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Spatial and Temporal Development of Autoimmune Vitiligo in Tyrosinase-Specific TCR Transgenic Mice

Abstract: Generalized vitiligo is thought to have an autoimmune etiology and has been correlated with the presence of CD8 T cells specific for melanocyte differentiation Ag. However, limited animal models for the disease have hampered its understanding. Thus, we generated TCR transgenic mice that recognize an epitope of the melanocyte protein, tyrosinase. These animals develop vitiligo with strikingly similar characteristics to the human disease. Vitiligo develops temporally and spatially, with juvenile lesions forming … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
96
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(108 citation statements)
references
References 59 publications
10
96
0
2
Order By: Relevance
“…Cxcr3−/− T cells were impaired in their ability to induce depigmentation (Figure 4A & B) and failed to accumulate in the skin (Figure 4C), despite normal numbers within the skin-draining lymph nodes (Figure 4D). This pattern is similar to that following treatment with IFNγ neutralizing antibody (26), and supports the observation that Cxcr3−/− TCR transgenic host mice are protected from vitiligo in a separate mouse model of hair depigmentation (33). In order to quantify the decreased efficiency of Cxcr3−/− T cell migration to the skin within the same host, we adoptively transferred equal numbers of CFP + WT PMEL T cells and GFP + WT or Cxcr3−/− PMEL T cells into hosts and measured their total numbers in the skin and skin-draining lymph nodes 5 weeks after transfer using flow cytometry.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…Cxcr3−/− T cells were impaired in their ability to induce depigmentation (Figure 4A & B) and failed to accumulate in the skin (Figure 4C), despite normal numbers within the skin-draining lymph nodes (Figure 4D). This pattern is similar to that following treatment with IFNγ neutralizing antibody (26), and supports the observation that Cxcr3−/− TCR transgenic host mice are protected from vitiligo in a separate mouse model of hair depigmentation (33). In order to quantify the decreased efficiency of Cxcr3−/− T cell migration to the skin within the same host, we adoptively transferred equal numbers of CFP + WT PMEL T cells and GFP + WT or Cxcr3−/− PMEL T cells into hosts and measured their total numbers in the skin and skin-draining lymph nodes 5 weeks after transfer using flow cytometry.…”
Section: Resultssupporting
confidence: 80%
“…Previous studies, including ours, reported that interfering with IFNγ prevents the onset of depigmentation in various mouse models of vitiligo, including genetic deficiency or antibody neutralization (26, 33). However successful treatment strategies should be able to reverse established disease through repigmentation, rather than simply prevent it.…”
Section: Discussionmentioning
confidence: 65%
“…Previous studies in mouse models of vitiligo have demonstrated that the development of vitiligo requires IFN-γ production by CD8 + T cells [13], and local IFN-γ release in the lesion promotes further recruitment of melanocytespecific CD8…”
Section: Discussionmentioning
confidence: 99%
“…Existing mouse models of vitiligo are generally established through specifically expressing exogenic protein in skin melanocytes, leading to the destruction of the melanocytes by CD8 + CTL targeting the exogenic antigen (9)(10)(11)(12). As a consequence, these vitiligo models do not authentically represent the activation mechanism of autoimmune CD8 + T cells in human vitiligo.…”
Section: Discussionmentioning
confidence: 99%